Young Entrepreneur, Parental Socioeconomic Status, and Financial Literacy: Does Supply Chain Mediate Entrepreneurship Education? - E.D Radianto, Wirawan; Yudhi Ari Wijaya, Oscarius; Syahrial, Ramon (International Journal of Supply Chain Management, 2020)
The purpose of this study was to examine the differences in the financial literacy of young entrepreneurs based on parental income, parental education level, and parental profession. Supply chain management significantly and positively mediates among the relationship between parental income, parental profession, parental education level, and financial literacy. This study used survey methods. The samples of this study were young entrepreneurs or students who started businesses. This study used a different test with smart-PLS. The results of this study showed the differences in the financial literacy of young entrepreneurs based on parental income, parental education level, and parental profession. This study found that young entrepreneurs with high or medium parental income were different from young entrepreneurs with low parental income. Young entrepreneurs with parents attending higher and secondary education were different from entrepreneurs with parents who are only attending elementary school. Young entrepreneurs who have parents as employees and entrepreneurs had no differences in financial, but different when compared to parents who work as laborers.